The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/pce.12783
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition by selenium is associated with changes in primary metabolism and nutrient levels in Arabidopsis thaliana

Abstract: Although Selenium (Se) stress is relatively well known for causing growth inhibition, its effects on primary metabolism remain rather unclear. Here, we characterized both the modulation of the expression of specific genes and the metabolic adjustments in Arabidopsis thaliana in response to changes in Se level in the soil. Se treatment culminated with strong inhibition of both shoot and root growth. Notably, growth inhibition in Se-treated plants was associated with an incomplete mobilization of starch during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Evidence that soluble sugars can be reduced has also been found. Ribeiro et al (2016) observed lower starch degradation at nightfall in Arabidopsis thaliana under increased Se conditions, as well as a reduction in the concentration of saccharides and hexoses in the same period.…”
Section: Photoassimilates and Photosynthetic Pigmentsmentioning
confidence: 68%
“…Evidence that soluble sugars can be reduced has also been found. Ribeiro et al (2016) observed lower starch degradation at nightfall in Arabidopsis thaliana under increased Se conditions, as well as a reduction in the concentration of saccharides and hexoses in the same period.…”
Section: Photoassimilates and Photosynthetic Pigmentsmentioning
confidence: 68%
“…Selenium increases the activity of amylases and invertases in mungbean, and application of Se could increase the soluble sugar concentration in the leaves of cowpea . On the other hand, evidence that soluble sugars can be reduced by Se has also been observed, due a lower starch degradation at nightfall in Arabidopsis thaliana under increased Se conditions, indicating that Se might inhibit starch degradation …”
Section: Discussionmentioning
confidence: 99%
“…29 On the other hand, evidence that soluble sugars can be reduced by Se has also been observed, due a lower starch degradation at nightfall in Arabidopsis thaliana under increased Se conditions, indicating that Se might inhibit starch degradation. 42 Furthermore, the concentrations in seeds of most elements to which PA might bind were unaffected by the application of selenate or selenite (Appendices F and G). Thus, Se biofortification of cowpea seeds would not appear to impact negatively on the bioavailability of other human and animal nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…9 The primary metabolism and the levels of some essential macro-and microelements are also affected by Se and these changes are associated with selenium-induced growth inhibition. 18,20 CONTACT Zsuzsanna Kolbert kolzsu@bio.u-szeged.hu.…”
Section: Known Molecular Mechanisms Of Selenium Toxicitymentioning
confidence: 99%